Salidroside alleviates sepsis-associated acute lung injury through modulation of the ERK/FoxO3a signaling axis and improvement of impaired autophagic flux - Xiangli Ma; Yurong Zhang; Zhenzhen Huang; Ling Zhang; Yujie Lin; Xu Fu; Peiwu Li (Molecular Biology Reports, 2026)

Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Influence mechanism of tritium exposure on the growth and microcystin synthesis of Microcystis aeruginosa under rising temperature - Xue Gong; Xin-wen Zhang; Ling-shu Xu; Chuan-dong Wang; Bao Zhang; Qian Fu; Qi-lin Dai; Jin-long Lai (Environmental Pollution, 2026)

Metal-polyphenol network-coated probiotic microcapsules: Enhancing Limosilactobacillus fermentum storage stability and yogurt characteristics - Yi-han Cai; Fang Huang; Si-ying Yan; Xiao-jin Lin; Shu-ling Huang; Shao-fu Feng; Jie-ying Chen; Yan-yan Huang; Xin-An Zeng; Xiang-ze Jia (International Dairy Journal, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Autophagy attenuates the secondary senescence of endometrial stromal cells induced by Bisphenol S - Xuguang Mi; Jianhua Fu; Lei Liu; Lingshan Wang; Shiling Chen; Mengxue Wu; Chunxue Niu; Yan Wang; Lixin Cao; Lin Wang; Ling Deng; Xiaodan Lu; et al. (Chemico-Biological Interactions, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Dynamic remodeling of intramuscular structural proteins and its impact on abalone muscle quality during post-mortem cold storage - Hua Liu; Tian-Bo Zhang; Fu-Hao Zhang; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Jia-Yin Huang; Min-Jie Cao; Yu-Lei Chen (Food Chemistry, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Multiscale modeling and swelling behaviors of Wyoming sodium montmorillonite systems - Zhi-jun Zhang; Jin-xiang Deng; Chang-fu Wei; Ya-kun Tian; Lin Hu; Min Wang; Ling-ling Wu; Kai-wen Tong (Computers and Geotechnics, 2026)

From passive prevention to proactive intervention: An AI-assisted integrated governance system for algal bloom monitoring and control - Minjuan Lin; Yihao Xu; Jia Peng; Yaoyang Chen; Yulong Zhu; Xuanye Fu; Yi Zhu; Ling Lin (Environmental Research, 2026)

Analysis of the AP2/ERF transcription factor family in Eriobotrya japonica and its role in exogenous melatonin-mediated regulation of salt stress - Ling Zhu; Fuhua Liu; Xin Lin; Tianyu Fu; Lin Zou; Yuanhai Pan; Rong Zou; Yang Zhao; Hanyao Zhang (Functional & Integrative Genomics, 2025)

Network pharmacology, molecular docking and experimental validation to elucidate the anti-ulcerative colitis mechanism of Rosa roxburghii Tratt. leaves - Ming-Liang Luo; Shuang Zhang; Qing-Yong Wang; Ling-Wei Fu; Li-Juan Xiang; Chang Lin; Xin Yin (Natural Product Research, 2025)

Pretrain-finetune neural operator for multi-fidelity surrogate modeling of structural dynamic systems - Pei-Lin Li; Shi-Fu Liu; Yi-Qing Ni; Jian-Ming Ling; You-Wu Wang (Engineering Structures, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

New natural products from Rhododendron ciliicalyx subsp. Lyi - Chun-Lin Guo; Si-Xuan Liu; Lu Zhang; Ling Li; Yong-Fu Lu; Si-Yang Dai; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2025)

Biohybrid microneedle delivering engineered probiotics for synergistic tumor gas/photothermal-immunotherapy - Wenxin Fu; Junhong Ling; A.M. Omer; Xiao-kun Ouyang; Lin Mei; Nan Wang (Chemical Engineering Journal, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Effects of 2-hydroxypropyl-β-cyclodextrin and 28-homobrassinolide on the physiological characteristics, gene expression and terpenoid indole alkaloid accumulation in Catharanthus roseus cambial meristematic cell cultures - Fangfang Fu; Haihua Li; Li Ling; Jiahe Li; Yifei Chen; Weijie Hu; Jiayu Li; Lin Ou; Zhaoxi Chen; Jun Li; Pengfei Zhou (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

The Efficacy of Cardiac Contractility Modulation for Treating Patients with Heart Failure - NingNing Zheng; YongBing Fu; MingZhu Xu; Lin Ling; TingBo Jiang; Feng Xue (Cardiovascular Engineering and Technology, 2025)

Insights into novel phosphorus-doped biochar for tetracycline removal: Non-radical oxidation and adsorption - Xi Fu; Xiaojun Niu; Dongqing Zhang; Ling Li; Xingyao Ye; Shan Liao; Maoyu Li; Chuting Lao; Deye Chen; Yu Lin; Zhiquan Yang (Journal of Environmental Chemical Engineering, 2024)

Biomimetic Stylophora pistillata-like NiMoO4/NiFeS crystalline–amorphous phase boundary activated lattice oxygen mechanism for efficient electrochemical water oxidation - Weikai Fan; Chaofan Liu; Jiang Wu; Hao Zhou; Tao Jia; Yang Ling; Ping He; Qunzhi Zhu; Zaiguo Fu; Mingze Ou; Jia lin; Zhongwei Chen (Chemical Engineering Journal, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Tough and biodegradable C-lignin cross-linked polyvinyl alcohol supramolecular composite films with closed-looping recyclability - Tao Gui; Ling-Ping Xiao; Shuang-Lin Zou; Yue Zhang; Xu Fu; Chang-Hao Liu; Run-Cang Sun (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Sulfation, characterization, antibacterial activity, and action mechanism of rice bran polysaccharides - Bing-Jie Chen; Yong-Jin Qiao; Gang Yu; Xiao Wang; Yi Zhang; Ling-Lin Fu (Food Bioscience, 2024)

Environmental concentrations of acetaminophen and its metabolites promote the spread of antibiotic resistance genes through pheromone signaling pathway - Xinyue Fu; Xiaobo Yang; Xiaoli Lin; Li Zhu; Panpan Yang; Feng Wang; Zhiqiang Shen; Jingfeng Wang; Yun Ling; Zhigang Qiu (Chemical Engineering Journal, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Influence of speed measurement method on performance of an electric-drive maize precision planter - Lin Ling; Guangwei Wu; Changkai Wen; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Jianhong Ding; Zhijun Meng; Bingxin Yan (Biosystems Engineering, 2024)

Human dental pulp stem cells have comparable abilities to umbilical cord mesenchymal stem/stromal cells in regulating inflammation and ameliorating hepatic fibrosis - Peixing Chen; Yanchun Lin; Wenbo Lin; Yun Li; Ting Fu; Yuanyue Liu; Tian Guan; Man Xin; Ling Ye; Peiluan Wang; Haoyu Zeng; Kaitao Yao (Human Cell, 2023)

Association between prenatal exposure to per- and polyfluoroalkyl substances and neurodevelopment in children: Evidence based on birth cohort - Xin-xin Gao; Qian-lin Zuo; Xi-hang Fu; Ling-ling Song; Man-qiu Cen; Jing Wu (Environmental Research, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Coupling the digital twin technology and life cycle assessment: Carbon dioxide emissions from polysilicon production - Shengqiang Yang; Zhiqiang Yu; Wenhui Ma; Lin Ma; Chaochun Li; Ling Fu; Ming Li; Zewen Zhao; Yuchen Yang (Sustainable Production and Consumption, 2023)

The epigenetic regulator Set9 harmonizes fungal development, secondary metabolism, and colonization capacity of Aspergillus flavus - Ling Hao; Mengjuan Zhang; Chi Yang; Xiaohua Pan; Dandan Wu; Hong Lin; Dongmei Ma; Yanfang Yao; Wangzhuo Fu; Jiarui Chang; Yanling Yang; Zhenhong Zhuang (International Journal of Food Microbiology, 2023)

Occurrence and carcinogenic risk assessment of N-nitrosamines in some dried aquatic products in China - Siting Huang; Wusheng Fu; Qinmei Fang; Lei Ni; Renjin Zheng; Ling Yong; Zheng Huang; Jie Pang; Zhong Lin; Honglin Lin; Rongde Dai (Food Control, 2023)

Accelerated verification method for the reliability of the motor drive mechanism of the corn precision seed-metering device - Changkai Wen; Jing Zhang; Kan Zheng; Hanqing Li; Lin Ling; Zhijun Meng; Weiqiang Fu; Bingxin Yan (Computers and Electronics in Agriculture, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Tiliroside induces ferroptosis to repress the development of triple-negative breast cancer cells - Chuang Hu; Jian-Fu Zhao; Yi-Ming Wang; Xian-lin Wu; Ling Ye (Tissue and Cell, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

SWD1 epigenetically chords fungal morphogenesis, aflatoxin biosynthesis, metabolism, and virulence of Aspergillus flavus - Xiaohua Pan; Ling Hao; Chi Yang; Hong Lin; Dandan Wu; Xuan Chen; Mengjuan Zhang; Dongmei Ma; Yu Wang; Wangzhuo Fu; Yanfang Yao; Shihua Wang; et al. (Journal of Hazardous Materials, 2023)

Late diagenetic alteration of carbonate evidenced by carbonate-deficient siliciclastic laminae - Xubin Wang; Lin Dong; Tong Li; Ziyi Wang; Changhu Zhang; Zhijun Jin; Jinhua Fu; Rukai Zhu; Kun Ling; Tianyu Wang (Chemical Geology, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Identification and Characterization of Bacillus subtilis B9: A Diazotrophic Plant Growth-Promoting Endophytic Bacterium Isolated from Sugarcane Root - Yi-ning Di; Ling Kui; Pratiksha Singh; Lu-feng Liu; Lin-yan Xie; Li-lian He; Fu-sheng Li (Journal of Plant Growth Regulation, 2023)
Plant endophytic microorganisms, which can enhance plant growth and resistance to biotic and abiotic stresses, are untapped resources with large potential applications for crop production. However, the endophytic community is influenced by multiple factors, such as host genetics, the environment, and other microbes. Thus, it is important to characterize well-adapted endophytes from native crops. We isolated 43 endophytic bacteria from sugarcane cultivar Yunzhe-99-91. All these 43 isolates were examined in vitro for nitrogenase activity and the ability to dissolve phosphorus and produce siderophore. One of these strains, B9, identified as Bacillus subtilis and showed maximum plant growth promotion, was selected for detailed studies. B9 promoted the production of organic acids such as propionic acid, acetic acid, malic acid and citric acid, and the production of phytohormones, including indole-3-acetic acid, cytokinin, 6-benzyladenine, and zeatin. Moreover, B9 significantly promoted the growth of sugarcane plantlets and increased the content of nitrogen, phosphorus, and potassium in the seedlings by 29.26%, 50.78%, and 15.49%, respectively. The photosynthetic rate, root development, and chlorophyll content were also improved with varying degrees compared to the non-inoculated control. The cotyledon and hypocotyl of sugarcane gems germinated faster when co-cultured with the B9 strain compared with control group. Colonization assay showed that B9 was mainly colonized in the roots, followed by the stems and leaves. In conclusion, the positive interaction between endophytic strain B9 and sugarcane may provide long-lasting benefits and a direction for developing and utilizing B9 as a biofertilizer for sugarcane cultivation to decrease fertilizer application.

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

An S-scheme CdS/K2Ta2O6 heterojunction photocatalyst for production of H2O2 from water and air - Cui Lai; Mengyi Xu; Fuhang Xu; Bisheng Li; Dengsheng Ma; Yixia Li; Ling Li; Mingming Zhang; Danlian Huang; Lin Tang; Shiyu Liu; Huchuan Yan; et al. (Chemical Engineering Journal, 2023)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Deformation characteristics and thresholds of the Tanjiawan landslide in the Three Gorges Reservoir Area, China - Fu-ling Zhang; Mao-lin Deng; Qing-lin Yi; Shu-qiang Lu; Wei-jun Zheng; Hai-feng Huang; Xing Zhu (Journal of Mountain Science, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

Reliability and Validity of a Mobile Device for Assessing Head Control Ability - Mohammad Nikkhoo; Chi-Chien Niu; Chen-Ju Fu; Meng-Ling Lu; Wen-Chien Chen; Yang-Hua Lin; Chih-Hsiu Cheng (Journal of Medical and Biological Engineering, 2021)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Regulation of Circadian Genes by the MAPK Pathway: Implications for Rapid Antidepressant Action - Xin-Ling Wang; Kai Yuan; Wen Zhang; Su-Xia Li; George Fu Gao; Lin Lu (Neuroscience Bulletin, 2020)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Overexpression of two cold-responsive ATAF-like NAC transcription factors from fine-stem stylo (Stylosanthes guianensis var. intermedia) enhances cold tolerance in tobacco plants - Peng-Lin Zhan; Shan-Wen Ke; Pan-Yu Zhang; Cong-Cong Zhou; Bei-Ling Fu; Xiang-Qian Zhang; Tian-Xiu Zhong; Shu Chen; Xin-Ming Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Phylogeographic analysis of porcine reproductive and respiratory syndrome virus 1 in Guangdong province, Southern China - Shao-Lun Zhai; Tao Lin; Xia Zhou; Zhang-Fu Pei; Zu-Zhang Wei; He Zhang; Xiao-Hui Wen; Qin-Ling Chen; Dian-Hong Lv; Wen-Kang Wei (Archives of Virology, 2018)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Dynamic assessment of rainfall-induced shallow landslide hazard - Yang Tang; Kun-long Yin; Lei Liu; Ling Zhang; Xiao-lin Fu (Journal of Mountain Science, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

First discovery of a Palaeoproterozoic A-type granite in southern Wuyishan terrane, Cathaysia Block: evidence from geochronology, geochemistry, and Nd–Hf–O isotopes - Zhi-Hong Chen; Ling Zhao; Dan-Dan Chen; Xi-Lin Zhao; Guang-Fu Xing (International Geology Review, 2017)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Rifampicin Loaded Mannosylated Cationic Nanostructured Lipid Carriers for Alveolar Macrophage-specific Delivery - Xu Song; Qing Lin; Ling Guo; Yao Fu; Jianfeng Han; Huan Ke; Xun Sun; Tao Gong; Zhirong Zhang (Pharmaceutical Research, 2015)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Microbial Source Tracking: A Tool for Identifying Sources of Microbial Contamination in the Food Chain - Ling-Lin Fu; Jian-Rong Li (Critical Reviews in Food Science and Nutrition, 2014)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Screening Chinese soybean genotypes for Agrobacterium-mediated genetic transformation suitability - Zhang-yue Song; Jing-luan Tian; Wei-zhe Fu; Lin Li; Ling-hong Lu; Lian Zhou; Zhi-hui Shan; Gui-xiang Tang; Hui-xia Shou (Journal of Zhejiang University-SCIENCE B, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Computational prediction and experimental assessment of an HLA-A*0201-restricted cytotoxic T lymphocyte epitope from neutral endopeptidase - Jingbo Zhang; Zhengcai Jia; Zhihua Lin; Jingyi Li; Xiaolan Fu; Yunjian Huang; Jinghong Zhao; Ling Nie; Weiping Hou; Fahuan Yuan; Yuzhang Wu (Immunologic Research, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

Differentiation of Fecal Escherichia coli from Human, Livestock, and Poultry Sources by rep-PCR DNA Fingerprinting on the Shellfish Culture Area of East China Sea - Hong-Jia Ma; Ling-Lin Fu; Jian-Rong Li (Current Microbiology, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

Free radical scavenging activity and antiproliferative potential of Polygonum cuspidatum root extracts - Yun-Wei Lin; Fu-Jung Yang; Chia-Ling Chen; Wei-Ting Lee; Ruey-Shyang Chen (Journal of Natural Medicines, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Genome sequence and characterization of a new virus infecting Mikania micrantha H.B.K. - Rui-Long Wang; Ling-Wen Ding; Qiao-Yang Sun; Jing Li; Zeng-Fu Xu; Shao-Lin Peng (Archives of Virology, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Using EEFM (Excitation Emission Fluorescence Matrix) to Differentiate the Organic Properties of the Effluents from the Ozonated Biofilters - Wen-Liang Lai; Lih-Fu Chen; Shao-Wei Liao; Shu-Lin Hsu; Li-Ho Tseng; Chang-Ling Miaw (Water, Air, & Soil Pollution, 2007)